Sulfated polysaccharide fraction from marine algae Solieria filiformis: Structural characterization, gastroprotective and antioxidant effects. (5th November 2016) - Sousa, Willer M.; Silva, Renan O.; Bezerra, Francisco F.; Bingana, Rudy D.; Barros, Francisco Clark N.; Costa, Luís E.C.; Sombra, Venicios G.; Soares, Pedro M.G.; Feitosa, Judith P.A.; de Paula, Regina C.M.; Souza, Marcellus H.L.P.; Barbosa, André Luiz R.; et al.
Highlights: Sulfated polysaccharide (SFP) possess a high sulfate content. The main constituent of the SFP is iota-carrageenan. SFP reduced the oxidative stress and the gastric damage in vivo . SFP also revealed the relevant antioxidant activity in vitro . Abstract: A sulfated polysaccharide (SFP) fraction from the marine alga Solieria filiformis was extracted and submitted to microanalysis, molar mass estimation and spectroscopic analysis. We evaluated its gastroprotective potential in vivo in an ethanol-induced gastric damage model and its in vitro antioxidant properties (DPPH, chelating ferrous ability and total antioxidant capacity). Its chemical composition revealed to be essentially an iota-carrageenan with a molar mass of 210.9 kDa and high degree of substitution for sulfate groups (1.08). In vivo, SFP significantly ( P  < 0.05) reduced, in a dose dependent manner, the ethanol-induced gastric damage. SFP prevents glutathione consume and increase of malondialdehyde and hemoglobin levels. SFP presented an IC50 of 1.77 mg/mL in scavenging DPPH. The chelating ferrous ability was 38.98%, and the total antioxidant capacity was 2.01 mg/mL. Thus, SFP prevents the development of ethanol-induced gastric damage by reducing oxidative stress in vivo and possesses relevant antioxidant activity in vitro .